Drug delivery of zinc to Barrett's metaplasia by oral administration to Barrett's esophagus patients. (March 2014) - Valenzano, Mary C; Mercado, Joanna M; Wang, Xuexuan; Zurbach, E Peter; Raines, Jonathan; McDonnell, Erin; Morgan, Melissa; Farrell, Christopher; Rudolph, David; Hwang, Austin; Barr, Maura; Cherian, Dinu; et al.
Background: Delivery of a pharmacologically effective drug dosage to a target tissue is critical. Barrett's epithelia are a unique challenge for drug delivery of orally administered zinc due to rapid transit down the esophageal lumen, incomplete absorptive differentiation of these epithelia, and the use of proton-pump inhibitor drugs abrogating intestinal uptake of supplemental zinc.Methods: Barrett's esophagus patients were administered oral zinc gluconate (26 mg zinc twice daily) for 14 days prior to biopsy procurement. Barrett's biopsies were analyzed for total zinc content by atomic absorption spectroscopy and by western immunoblot for cellular proteins known to be regulated by zinc.Results: Cellular levels of both the Znt-1 transport protein and the alpha isoform of PKC were over 50% lower in the zinc treatment group.Conclusion: Oral zinc administration can result in effective delivery of zinc to Barrett's epithelia with resulting effects on intracellular signal transduction.